Именем закона: [повести] / Николай Томан - Томан Николай Владимирович (Сделано в СССР, 2016)
Экземпляры: ф.1 (20240126) / Инвентарный номер: 64210 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: Т 56 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-445.7